IMPLEMENTATION OF THE STANDARD OPERATING PROCEDURE (SOP) FOR KINESIOLOGICAL ULTRASOUND (KUS) FOR PHYSICAL THERAPISTS (REMUNOM, 2025)
Objective: To implement the Standard Operating Procedure (SOP) of Kinesiological Ultrasound (KUS) for Physical Therapists in a public hospital located in Teresina, Piauí. Methods: This is an experience report based on a methodological strategy of an intervention project. Results and Discussion: An SOP was developed based on the assessment challenges using KUS. Subsequently, a brainstorming session and a presentation of this document were held with some of the hospital’s physical therapists in a virtual Google Meet room, where suggestions and barriers were listed in response to the trigger question: In your opinion, what will we need to implement the KUS SOP in order to overcome the existing obstacles in this institution? After these processes, training and capacity-building sessions were conducted for the ICU physical therapy teams of the hospital. Final Considerations: Furthermore, the effective implementation of the kinesiological ultrasound protocol was achieved among the physical therapy teams working in the intensive care units of the hospital in question. The clinical benefits are already being observed and will be even more evident in the near future through the execution of this work